CVC-STAR: Protecting data confidentiality while increasing flexibility and quality of responses. (2nd June 2008) - Rice, Daniel O.; Garfinkel, Robert; Gopal, Ram
Confidentiality via Camoufiage (CVC) provides a practical method for giving unlimited, correct, numerical responses to ad-hoc queries to an on-line database, while not compromising confidential numerical data. CVC-POL guarantees confidentiality by hiding protected data points in a polytope and generating query answers over the polytope. In this paper we introduce CVC-STAR, which protects confidential data using a set defined by a union of line segments resembling a star. Solutions for determining CVC-STAR interval answers are given for several common query types. Computational experience shows that the answers for CVC-STAR are superior to those of CVC-POL while providing more robust confidentiality protection.